2005
DOI: 10.1159/000087785
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Alexithymia and Its Relationships with the ‘Big Five’ Factors, Temperament, Character, and Attachment Style

Abstract: Background: Controversy still exists concerning the stability of the alexithymia construct. Also, although alexithymia has been found to be related in a theoretically meaningful way to other personality constructs such as the ‘Big Five’ factors, few studies have investigated its relationship with influential constructs such as temperament and character, and attachment security. Methods: Two hundred twenty-one undergraduate and graduate students were administered the Toronto Alexithymia Scale (TAS-20), the Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
67
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 67 publications
15
67
0
6
Order By: Relevance
“…This supports the conclusions of Grabe et al and Picardi et al that both genetic (temperament) and environmental (character) dimensions of personality contribute to the alexithymia construct. 24,26 Alexithymic deficits in emotion regulation are related to the reduced ability to control, regulate, and adapt behavior according to chosen goals and values that characterize individuals with low self-directedness. Alexithymic deficits in emotion regulation are also plausibly related to cautiousness, fearfulness, pessimism, and shyness in individuals who score high in harm avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the conclusions of Grabe et al and Picardi et al that both genetic (temperament) and environmental (character) dimensions of personality contribute to the alexithymia construct. 24,26 Alexithymic deficits in emotion regulation are related to the reduced ability to control, regulate, and adapt behavior according to chosen goals and values that characterize individuals with low self-directedness. Alexithymic deficits in emotion regulation are also plausibly related to cautiousness, fearfulness, pessimism, and shyness in individuals who score high in harm avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a healthy college student sample, Picardi et al measured alexithymia with the TAS-20 and reported that alexithymia was correlated with both temperament and character dimensions of personality, indicating that both genetic and environmental factors might contribute to alexithymia development. 26 In that study the TAS-20 total and subscale scores were correlated with harm avoidance, low self-directedness, low cooperativeness, and low reward dependence.…”
mentioning
confidence: 85%
“…Because we were interested in three out of the four temperament dimensions and none of the character dimensions, we administered only 55 items from the TCI-125 (i.e., items that comprised the NS, HA, and RD scales). 1 The TCI-125 has been used in numerous previous studies (Akiskal et al, 2005;Picardi, Toni, & Caroppo, 2005;Smith, Duffy, Stewart, Muir, & Blackwood, 2005). This scale correlates with other related measures of temperament (Akiskal et al, 2005), has acceptable internal consistencies (Chakroun-Vinciguerra, Faytout, Pèlissolo, & Swendsen, 2005), has the same factor structure as the standard TCI (Chakroun-Vinciguerra et al, 2005), and demonstrates associations with demographic characteristics that are similar to the original questionnaire (Chakroun-Vinciguerra et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…[77] Aleksitimi skorlarının, klinik popülasyon-dakine kıyasla, klinik olmayan popülasyonda daha istikrarlı olması da bu bilgi ile tutarlı görünmektedir. [78][79][80] Ne var ki, aleksitiminin uzun süreli/kalıcı bir özellik mi yoksa geçici bir durum mu olduğu günümüzde hala netliğe kavuşamamış bir konudur.…”
Section: Aleksitimi Kavramıyla İlgili Sorgulamalar Ve Yeni Açılımlarunclassified